Fast MVCT: A rapid imaging method for total body or marrow irradiation in helical tomotherapy - Magome, Taiki (Int J Radiat Oncol Biol Phys, 2016)
PURPOSE: Megavoltage computed tomography (MVCT) imaging has been widely used for three-dimensional (3-D) setup of patients treated with helical tomotherapy (HT). One drawback of MVCT is it's very long imaging time, owing to slow couch speeds of approximately 1 mm/s, which can be difficult for the patient to tolerate. We sought to develop an MVCT imaging method allowing faster couch speeds, and to assess its accuracy for image guidance for HT. METHODS AND MATERIALS: Three cadavers were scanned four times with couch speeds of 1, 2, 3, and 4 mm/s. The resulting MVCT images were reconstructed using an iterative reconstruction (IR) algorithm with a penalty term of total variation, as well as with a conventional filtered back projection (FBP) algorithm. The MVCT images were registered with kilovoltage CT images, and the registration errors from the two reconstruction algorithms were compared. This fast MVCT imaging was tested in three cases of total marrow irradiation as a clinical trial. RESULTS: Three-dimensional registration errors of the MVCT images reconstructed with the IR algorithm were smaller than the errors of images reconstructed with the FBP algorithm at fast couch speeds (2, 3, 4 mm/s). The scan time and imaging dose at a speed of 4 mm/s were reduced to 30% of those from a conventional coarse mode scan. For the patient imaging, faster MVCT (3 mm/s couch speed) scanning reduced imaging time and still generated images useful for anatomical registration. CONCLUSIONS: Fast MVCT with IR algorithm is clinically feasible for large 3-D target localization, which may reduce overall time for treatment procedure. This technique may also be useful for calculating daily dose distributions or organ motion analyses in HT treatment over a wide area. Automated integration of this imaging is at least needed to further assess its clinical benefits.